Neurokinin 1 receptor inhibition alleviated mitochondrial dysfunction via restoring purine nucleotide cycle disorder driven by substance P in acute pancreatitis - Chenxia Han; Lu Li; Lin Bai; Yaling Wu; Jiawang Li; Yiqin Wang; Wanmeng Li; Xue Ren; Ping Liao; Xiaoting Chen; Yaguang Zhang; Fengzhi Wu; et al. (Acta Pharmaceutica Sinica B, 2025)
Acute pancreatitis (AP) is a life-threatening gastrointestinal disorder for which no effective pharmacological treatments are currently available. One of the pharmacological targets that merits further research is the neurokinin 1 receptor (NK1R), which is found on pancreatic acinar cells and responds to the neuropeptide substance P (SP) that participates in AP. Although a few studies have stated the involvement of SP/NK1R in neurogenic inflammation in AP development, the regulatory mechanism remains unclear. In this study, we found that following activation of NK1R by SP, β-arrestin1, a scaffold protein of NK1R, down-regulated transcription of Adss, Adsl, and Ampd in the purine nucleotide cycle, thereby inhibiting mitochondrial function through fumarate depletion. Interestingly, we identified magnolol as a new and natural NK1R inhibitor with a non-nitrogenous biphenyl core structure. It exhibited a beneficial effect on AP by restoring purine nucleotide cycle metabolic enzymes and fumarate levels. Our study not only provides new therapeutic strategies, leading compounds, and drug translation possibilities for AP, but also provides important clues for the study of downstream mechanisms driven by SP in other diseases.